Advances in Remote Sensing-based Disaster Monitoring and Assessment - Im, Jungho; Park, Haemi; Takeuchi, Wataru (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Remote sensing data and techniques have been widely used for disaster monitoring and assessment. In particular, recent advances in sensor technologies and artificial intelligence-based modeling are very promising for disaster monitoring and readying responses aimed at reducing the damage caused by disasters. This book contains eleven scientific papers that have studied novel approaches applied to a range of natural disasters such as forest fire, urban land subsidence, flood, and tropical cyclones.